PEMBERDAYAAN KELUARGA TANGGUH DIGITAL MELALUI KELOMPOK PKK DESA MUNDAM KOTA DUMAI PROVINSI RIAU - Daherman, Yudi; Handayani, Benni; Afdhol, Muhammad Khairul (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
The presence of the digital era is currently a challenge for society in the values of life in the family. Empowerment and family welfare (PKK) in Mundam village, Medang Kampai sub-district, Dumai city, are experiencing the challenges of the digital era. The priority issue in this service activity is to raise awareness of PKK members in becoming a digital resilient family. Digital literacy is the first ability to think critically when consuming information in cyberspace. Family members should have immunity in consuming information with the power to think critically, by questioning and discussing the information obtained. The concept of Interpersonal communication is a concept of intense communication between parents and children in the family at home. The aim of this program is to create conditions for the PKK in Mundam village to have digital literacy so that a digitally resilient family is achieved. There are two literacy programs that are important to carry out, namely a digital resilient family and well-executed interpersonal communication. The two programs are one of the solutions in minimizing the problems faced by PKK in Mundam village.